The Manhattan project - A part of physics history - Mårtensson-Pendrill, Ann Marie ; 0000-0002-1405-6561 (Physics Education, 2006)
Current physics textbooks tend to exclude military applications, but it is explained here how a study of the Manhattan project-the devastatingly successful attempt to develop an atomic bomb-can show students how the lives and work of physicists are shaped by events in society. Much of the original source material is available in books and on the internet (and referenced here), which allows students to discover the views of the scientists for themselves.